Mechanical properties of bamboo reinforced epoxy sandwich structure composites - Roslan S.A.H.; Hassan M.Z.; Rasid Z.A.; Zaki S.A.; Daud Y.; Aziz S.; Sarip S.; Ismail Z. (Universiti Malaysia Pahang, 2024)
In the composite industry, natural fibres have great potential to replace synthetic fibres like carbon and glass, due to their low cost and environmentally friendly materials. Bamboo is emerging as a versatile reinforcing fibre candidate because this woody plant has a number of advantages, such as being naturally strong, biodegradable and abundantly available. In this study, a compression test with a crosshead displacement rate of 1 mm/min was conducted on square and triangular honeycomb core structures based on bamboo-epoxy composites so as to study their specific energy absorption. Both square and triangular honeycomb structures were manufactured by the slotting technique. Initially, a tensile test with the same crosshead displacement rate was conducted to study the tensile strength of unidirectional bamboo-epoxy composites with 0, 45 and 90 fibre orientations. Bamboo-epoxy composite laminates were fabricated by applying a hand lay-up technique. The experimental data showed that the unidirectional bamboo-epoxy composite with 0 orientation offered the highest tensile strength. This indicates that the bamboo is stronger when parallel to the tensile axis. Meanwhile, the triangular honeycomb bamboo-epoxy structure offered about 10% more energy absorption than the square honeycomb structure, which indicates that the smaller cell size of honeycomb is able to absorb more energy than the bigger one. Universiti Malaysia Pahang.